Microplankton bloom in a brackish water lagoon of Terengganu - Shamsudin, Lokman; Shazili, N.A.M. (Springer Science and Business Media LLC, 1991)
Increased primary plankton productivity was observed in a brackish water lagoon of Terengganu during the study period between January 1988 to December 1988. The lagoon is also the site for the fish cage culture activities of sea bass during the study period. An examination of water quality at the sampling stations during the study period indicated that both the organic and inorganic nutrients were high during the pre-monsoon period. The source of the nutrient in the lagoon was believed to be derived from the agro-based industrial effluents, fertilisers from paddy fields as well as untreated human and animal wastes. This coincided with the peak production of plankton in the surface waters of the brackish water lagoon. During this period both cultured and indigenous fish species were seen to suffer from oxygen asphyxiation (suffocation due to lack of oxygen). The primary productivity values ranged from 9 to 22 μg/L/h during the peak period while the microplankton species were composed of diatom, flagellates and dinoflagellates. Reduction in the primary productivity values were obtained with reduction in sallinity, specially during the peak monsoon months (November to March) corresponding to the Northeast monsoon period.